2019
DOI: 10.1002/mcf2.10070
|View full text |Cite
|
Sign up to set email alerts
|

First Observations of Long‐Distance Migration in a Large Skate Species, the Winter Skate: Implications for Population Connectivity, Ecosystem Dynamics, and Management

Abstract: The overexploitation and decline of groundfish populations throughout the 1980s and 1990s resulted in a regime shift on Georges Bank and southern New England, which was characterized by subsequent exponential increases in the observed biomass of Winter Skate Leucoraja ocellata in the region. Recent work suggested that the rate of the Winter Skate biomass increase cannot be fully explained by internal population dynamics of a population without immigration from other regions and/or populations and that adult‐me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Mature individuals are present in our study regions, although less common than places like a known aggregation site, nicknamed "Tiger Beach, " off The Little Bahama Bank (Hammerschlag et al, 2017). As such, there may be fine-scale genetic underpinnings to these differential migration dynamics, as seen in other elasmobranchs (e.g., winter skate, Frisk et al, 2019), although this remains unknown. Caribbean reef sharks in the present study exhibited high site fidelity to relatively constricted regions of fringing coral reef habitat adjacent to the continental shelf drop off (Tongue of the Ocean in New Providence, Exuma Sound in the Exumas), which supports previous work on this species (Chapman et al, 2005;Shipley et al, 2018).…”
Section: Discussionmentioning
confidence: 86%
“…Mature individuals are present in our study regions, although less common than places like a known aggregation site, nicknamed "Tiger Beach, " off The Little Bahama Bank (Hammerschlag et al, 2017). As such, there may be fine-scale genetic underpinnings to these differential migration dynamics, as seen in other elasmobranchs (e.g., winter skate, Frisk et al, 2019), although this remains unknown. Caribbean reef sharks in the present study exhibited high site fidelity to relatively constricted regions of fringing coral reef habitat adjacent to the continental shelf drop off (Tongue of the Ocean in New Providence, Exuma Sound in the Exumas), which supports previous work on this species (Chapman et al, 2005;Shipley et al, 2018).…”
Section: Discussionmentioning
confidence: 86%
“…However, the recent use of electronic tags has provided increased insight into their movement (Siskey et al, 2019). Studies have shown finescale interspecific depth separation (Humphries et al, 2016) and seasonal offshore movements (Hunter et al, 2005), with extensive migrations through coastal waters reported for some species of skate (King and McFarlane, 2010;Farrugia et al, 2016;Frisk et al, 2019). Site fidelity to coastal areas has also been shown in several species (Ellis et al, 2011;Neat et al, 2014;Sousa et al, 2019), including in relation to nursery grounds (Hunter et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…(2019) for Winter Skate Leucoraja ocellate across the NW Atlantic, and the authors attributed those findings to foraging in specified geographic areas, requiring extensive movements. These findings were later supported by passive acoustic telemetry (Frisk et al., 2019). Movement to specific foraging grounds seems unlikely for both L .…”
Section: Discussionmentioning
confidence: 76%